HUBUNGAN PENGETAHUAN PENDERITA TUBERKULOSIS PARU DENGAN KEPATUHAN DALAM PROGRAM PENGOBATAN TUBERKULOSIS PARU DI PUSKESMAS CIJAGRA LAMA - Siti Rahayu; Stevani Basry; Andi sukandi (Jurnal Kesehatan, 2023)
Knowledge is a very important domain for the formation of one's actions. Increased knowledge can lead to changes in perceptions, habits and beliefs of pulmonary tuberculosis sufferers in carrying out treatment programs. This research was conducted with the aim of finding out the relationship between knowledge of pulmonary tuberculosis patients and compliance of tuberculosis sufferers in the pulmonary tuberculosis treatment program at the Cijagra Lama Community Health Center using a descriptive correlation design as the research design. The instrument was made in the form of a questionnaire and divided into 2 parts, namely a questionnaire to measure knowledge using the Guttman scale and a questionnaire to measure compliance using a Likert scale. The number of samples studied was 32 people using convenience sampling techniques. Based on statistical analysis of Spearman's correlation on degrees of freedom with α = 0.05, a value of ρ = 0.337 and a value of p = 0.059 were obtained for the relationship between knowledge and compliance. This is a moderate positive relationship with adequate interpretation between knowledge and compliance of tuberculosis sufferers in the pulmonary tuberculosis treatment program. For further research related to the compliance of pulmonary tuberculosis sufferers in carrying out the pulmonary tuberculosis treatment program, it is deemed necessary to examine other factors that influence the compliance of pulmonary tuberculosis sufferers in carrying out the treatment program.